Superior field emission properties of layered WS2-RGO nanocomposites - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Scientific Reports, 2013)
We report here the field emission studies of a layered WS2-RGO composite at the base pressure of similar to 1 x 10(-8) mbar. The turn on field required to draw a field emission current density of 1 mu A/cm(2) is found to be 3.5, 2.3 and 2 V/mu m for WS2, RGO and the WS2-RGO composite respectively. The enhanced field emission behavior observed for the WS2-RGO nanocomposite is attributed to a high field enhancement factor of 2978, which is associated with the surface protrusions of the single-to-few layer thick sheets of the nanocomposite. The highest current density of similar to 800 mu A/cm(2) is drawn at an applied field of 4.1 V/mu m from a few layers of the WS2-RGO nanocomposite. Furthermore, first-principles density functional calculations suggest that the enhanced field emission may also be due to an overalp of the electronic structures of WS2 and RGO, where graphene-like states are dumped in the region of the WS2 fundamental gap.

Enhanced field emission properties of doped graphene nanosheets with layered SnS2 - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Applied Physics Letters, 2014)
We report here our experimental investigations on p-doped graphene using tin sulfide (SnS2), which shows enhanced field emission properties. The turn on field required to draw an emission current density of 1 mu A/cm(2) is significantly low (almost half the value) for the SnS2/reduced graphene oxide (RGO) nanocomposite (2.65 V/mu m) compared to pristine SnS2 (4.8 V/mu m) nanosheets. The field enhancement factor beta (similar to 3200 for the SnS2 and similar to 3700 for SnS2/RGO composite) was calculated from Fowler-Nordheim (F-N) plots, which indicates that the emission is from the nanometric geometry of the emitter. The field emission current versus time plot shows overall good emission stability for the SnS2/RGO emitter. The magnitude of work function of SnS2 and a SnS2/graphene composite has been calculated from first principles density functional theory (DFT) and is found to be 6.89 eV and 5.42 eV, respectively. The DFT calculations clearly reveal that the enhanced field emission properties of SnS2/RGO are due to a substantial lowering of the work function of SnS2 when supported by graphene, which is in response to p-type doping of graphene. (C) 2014 AIP Publishing LLC.

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

Negative infrared photocurrent response in layered WS2/reduced graphene oxide hybrids - Ratha, Satyajit; Simbeck, Adam J.; Late, Dattatray J.; Nayak, Saroj K.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
We report high performance IR photocurrent response of two-dimensional hybrid materials consisting of layered WS2 nanosheets and reduced graphene oxide (RGO). Comparative photocurrent response studies of WS2 nanosheets, RGO, and WS2/RGO hybrids were carried out by performing current-voltage (I-V) and time-dependent current measurements with a laser excitation source having a wavelength of 808 nm. The experimental investigations indicate that WS2/RGO hybrids show negative photocurrent response, whereas WS2 and RGO show positive photocurrent response. The negative photocurrent response of the WS2/RGO hybrids is explained using a band alignment diagram and attributed to a charge transfer mechanism between WS2 and RGO. This analysis is further corroborated by first-principles density functional calculations. The fabricated device based on WS2/RGO hybrids shows a photosensitivity R-lambda of about 6 AW(-1) and a quantum efficiency eta of similar to 924%, which demonstrates high sensitivity of the hybrid material towards IR detection. WS2/RGO hybrids are therefore promising candidates for potential applications in optoelectronic circuits and low cost, high performance, and reliable photodetectors. (C) 2014 AIP Publishing LLC.

Synthesis of a 3D free standing crystalline NiSex matrix for electrochemical energy storage applications - Dinara, Syed Mukulika; Samantara, Aneeya K.; Das, Jiban K.; Behera, J. N.; Nayak, Saroj K.; Late, Dattatray J.; Rout, Chandra Sekhar (Dalton Transactions, 2019)
The electrochemical performance for energy storage of three-dimensional (3D) self-supported heterogeneous NiSex cubic-orthorhombic nanocrystals grown by a facile one-step chemical vapour deposition (CVD) approach on Ni foam substrates has been explored. NiSex shows a high specific capacitance of 1333 F g(-1) with ultra-high energy (105 W h kg(-1)) and power (54 kW kg(-1)) densities. Furthermore, by integrating the as-grown NiSex as the anode and reduced graphene oxide as the cathode, a hybrid super-capacitor (HSC) prototype with a coin cell configuration has been fabricated. The device shows better capacitance (40 F g(-1)) with high energy (22 W h kg(-1)) and power (5.8 kW kg(-1)) densities and robust cycling durability (similar to 88% capacitance retention after 10 000 repeated cycles). For practical reliability of the as-fabricated HSC, a red LED has been illuminated by connecting it with two charged coin cells. These outstanding performances of the HSC prove to be promising for applications in high energy storage systems.